Treatment Optimization for Brain Metastasis from Anaplastic Lymphoma Kinase Rearrangement Non-Small-Cell Lung Cancer - Wang, Wenhui (Oncol Res Treat, 2019)
BACKGROUND: Brain metastasis is common in non-small-cell lung cancer (NSCLC) with driver gene mutations. Anaplastic lymphoma kinase (ALK) gene rearrangement is one of the common driver mutations in NSCLC. Tyrosine kinase inhibitor (TKI) has been the research hotspot at present. However, there are relatively few studies specified on the treatment of brain metastasis from ALK gene rearrangement NSCLC. The prognosis of these patients, the role of ALK-TKI, and the proper combination model of ALK-TKI with radiotherapy are worth further exploring. This review focuses on new data on the prognosis of ALK-TKI and the proper combination model of ALK-TKI with radiotherapy. SUMMARY: According to some retrospective trials, for ALKi-naïve ALK rearrangement NSCLC patients with brain metastasis, crizotinib together with radiotherapy seem to improve intracranial control rate, progression-free survival, and very likely improve overall survival; next-generation ALK-TKIs are now replacing crizotinib as first-line treatment. For patients with central nervous system progression during crizotinib application, combining radiotherapy could improve the local control rate while continuing crizotinib to control systemic disease. Second-/third-generation ALK inhibitors had higher intracranial ORR and DCR even after crizotinib-refractory situations, and they alone had a strong efficacy against intracranial tumors, in which situation radiotherapy might be omitted. Stereotactic radiosurgery (SRS) and whole-brain radiotherapy (WBRT) were both local treatment options for brain metastasis, and the preferred choice was hard to make. ALK resistance is complicated with a wide range of molecular changes, and future studies are needed to solve these problems. Anyway, further and larger prospective studied are worth exploring to offer a confirmed preferred choice of drugs and radiation. KEY MESSAGES: Next-generation ALK-TKIs are now replacing crizotinib as first-line treatment in ALKi-naïve ALK rearrangement NSCLC patients with brain metastasis, and they alone might have a strong efficacy against intracranial tumors in crizotinib-refractory situations in which occasion radiotherapy might be omitted. SRS and WBRT are both local treatment options for brain metastasis.